The South Asia to Gulf Migration Governance Complex - Ennis, Crystal A.; Blarel, Nicolas (Bristol University Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. The Gulf is a major global destination for migrant workers, with a majority of these workers coming from South Asia. In this book, a team of international contributors examine the often-overlooked complex governance of this migration corridor. Going beyond state-centric analysis, the contributors present a multi-layered account of the 'migration governance complex.' They offer insights not only into the actors involved in the different components of migration governance, but also into the varying ways of interpreting and explaining the meaning and value of these interactions. Together, they enable readers to better understand migration in this important region, while also providing a model for analyzing global migration governance in practice in different parts of the world.